Obcy wśród obcych. Julian Tuwim i rosyjscy emigranci - Mitzner, Piotr (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2014)
Julian Tuwim was an accomplished translator of Russian poetry. Until recently, his contacts with the Russian emigrants in Poland in the interwar period had been scarcely known. The article expands on the topic of the influence of Tuwim’s poetry on the members of the Russian emigration and attempts to describe his role in the life of the Russian diaspora. What is even more interesting, Tuwim maintained his Russian relations also in the communist Poland, helping and supporting those who were forced to hide their past. Members of the Russian emigration (especially a distinguished critic Dymitr Fiłosofow) held Tuwim’s poetry in hight esteem, and they also appreciated him as a gifted translator. The article builds its critical argument on rare texts published in Russian emigration periodicals, archives and the post-war writings of Leon Gomolicki.